Research on the Assessment of Architectural Colors in Cultural Heritage Blocks Based on Computer Vision: A Case Study of Tianjin - Xiaoli Cao; Yingxia Yun; Lijian Ren (Land)
Historic and cultural heritage districts, as physical carriers of a city’s cultural identity, have become key issues in urban development. Architectural color, as a core visual element of district character, is an important symbol of regional identity recognition. However, further exploration is needed regarding how to integrate architectural color quantification metrics and evaluation techniques into the urban characteristics management framework. In this paper, taking Tianjin’s historic cultural heritage districts as a case study, street view data were utilized, and deep learning along with clustering analysis methods were employed to extract architectural colors. Based on the “point-line-surface” protection strategy, a multi-scale architectural color identification and evaluation method spanning “buildings-streets-districts” was established. This methodology enables the recognition of dominant building colors in heritage zones at the district scale and the assessment of street color harmony and richness at the street scale. By analyzing these two levels, this research interprets the role of architectural color as a visual attribute in defining urban character and enhancing urban distinctiveness. It provides technical support for refining urban characteristics management systems and achieving precise control over the preservation and development of distinctive urban features.